Metabolic storm in psoriatic arthritis: a cardiovascular time bomb? - Eugeniu Russu; Mircea Betiu; Alexandru Corlateanu; Lia Chislari; Larisa Rotaru; Liliana Groppa (Folia Medica)
Introduction: Psoriatic arthritis (PsA) is a chronic immune-mediated disease that extends beyond joint and skin involvement, being strongly associated with metabolic disturb ances and increased cardiovascular risk. Chronic inflammation, adipokine imbalance, and endothelial dysfunction contribute to accelerated atherosclerosis in this population. Aim: To assess the interrelationships between systemic inflammation, lipid metabolism, leptin levels, and subclinical atherosclerosis in PsA patients, with the goal of improving cardiovascular risk stratification and management. Materials and methods: A total of 256 PsA patients and 150 matched healthy controls were enrolled. Clinical evaluations included disease activity indices, BMI, and waist circumference. Biochemical assessments comprised lipid profile, leptin, and high-sensitivity C-reactive protein (hs-CRP). Carotid intima-media thickness (IMT) and plaque formation were evaluated via ultrasonography. Statistical comparisons were made using non-parametric and chi-square tests. Results: PsA patients exhibited significantly higher levels of total cholesterol (5.9 mmol/L vs. 5.0 mmol/L), triglycerides (1.2 mmol/L vs. 0.5 mmol/L), low-density lipoprotein cholesterol (4.0 mmol/L vs. 3.5 mmol/L), and atherogenic coefficient (3.5 vs. 2.6), with p-values <0.001 for all. High-density lipoprotein cholesterol levels did not differ significantly. Obesity was five times more frequent in PsA (BMI >30 kg/m2), and leptin was elevated in 58% of PsA patients versus 8% of controls. Leptin levels correlated positively with hs-CRP (R=0.59) and BMI (R=0.75). Increased hs-CRP levels were associated with thicker IMT, more frequent plaque formation, and higher prevalence of coronary artery disease. Patients with hs-CRP >10 mg/L had the greatest cardiovascular burden. Conclusion: This study confirms that PsA is associated with significant pro-atherogenic lipid disturbances, obesity, elevated leptin levels, and subclinical atherosclerosis. The integration of lipid profile, leptin, and hs-CRP with vascular imaging offers a practical framework for early cardiovascular risk assessment. Multidisciplinary management, including metabolic and inflammatory targets, is essential for improving long-term outcomes in PsA patients.